Adsorption of Nitrite (NO2-) Using Natural Zeolite and Natural Zeolite Modified with Cetyl Trimethylammonium Bromide (CTAB) - Hanan, Ihsan Sofyan; Hakim, Muhammad Fahmi Hakim; Pambudi, Teguh (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Nitrite contamination in water is a critical environmental and public health concern due to its toxicity and persistence. This study investigates the adsorption of nitrite using activated natural zeolite and CTAB-modified zeolite through batch experiments. Natural zeolite was activated with 1M HCl to enhance its surface area, while modification with cetyl trimethylammonium bromide (CTAB) was performed to improve anion adsorption capacity. Adsorption experiments were conducted at different pH levels (2, 4, 6, 8) and contact times (10–90 minutes) using a 100 ppm nitrite solution, with 0.2 g of adsorbent in 50 mL solution. Residual nitrite concentrations were analyzed using UV-Vis spectrophotometry. The results showed that the optimum pH for activated zeolite was 4, with a residual nitrite concentration of 0.108 mg/L, whereas CTAB-modified zeolite performed best at pH 2, reducing nitrite to 0.005 mg/L. The optimal adsorption times were 60 minutes for activated zeolite (0.0106 mg/g) and 75 minutes for CTAB-modified zeolite (0.0156 mg/g). Kinetic analysis indicated that activated zeolite followed a pseudo-first-order model (R² = 0.950), while CTAB-modified zeolite was influenced by intraparticle diffusion (R² = 0.764). These findings highlight the potential of zeolites as efficient and cost-effective adsorbents for nitrite removal in wastewater treatment.